Concepções do professor do ensino médio relativas à densidade do conjunto dos números reais e suas reações frente a procedimentos para a abordagem desta propriedade - Penteado, Cristina Berndt (2004)
The work approaches the subject of the density of the real numbers, here taking in the direction of the existence of infinite rational numbers and infinite irrationals between two distinct real numbers. Some research evidences difficulties of the students in the classification of rational numbers and irrationals, as well as the unfamiliarity of the property of the density of the set of the real numbers. The objective of the study is to investigate the conception and the reaction of the teachers of high-school front to the different registers of representations of the numbers, when analyzed the property of the density, as much the density of the set of the rational numbers in the set of the real numbers how much of the irrationals in reals. Is considered to investigate it the viability of two types of distinct procedures for the attainment of real numbers between two supplied: the procedure of the arithmetic mean and other inspired in the process of diagonal line of Cantor, using the representation decimal of the real numbers. For in such a way it was carried through an intervention by means of the elaboration, application and analysis of an education sequence, composed of ten activities, based in the Theory of the Registers of Representation Semiotics of Raymond Duval. The education sequence was based on principles of the Didactic Engineering of Michèle Artigue. Although to evidence envolvement of the participants, some difficulties identified in the research persist as for example, the association of the infinite representation with irrationality and the identification of a rational number as being only that one that has finite representation. Some teachers had demonstrated the intention to apply similar questions to the ones of the sequence, to its students of high-school